Postpartum contraceptive use after vaginal and caesarean birth in Nigeria: a nationwide population-based analysis - Otobo I Ujah; Omoregie Irowa; Ferdinand C Obi; Christopher O Egbodo; Innocent A O Ujah (BMJ Public Health)
Background Despite prior research suggesting that the mode of delivery (MOD) may influence subsequent postpartum behaviour, limited evidence exists about how contraceptive use and method choice differ following caesarean section (CS) compared with vaginal delivery (VD). This study aimed to explore variation in self-reported postpartum contraceptive use by MOD and to examine whether MOD was associated with contraceptive method choice among a nationally representative sample of postpartum women in Nigeria.Methods We analysed nationally representative cross-sectional data from the 2021 Nigeria Multiple Indicator Cluster Survey. The study sample included all women aged 15–49 years who had a live birth in the 2 years preceding the survey (n=4277). We employed multivariable logistic regression to assess the association between MOD and any postpartum contraceptive use and multinomial logistic regression to evaluate the association between MOD and contraceptive method choice (categorised as highly effective, moderately effective or least effective).Results Overall, 1074 women (28.7%) reported using a contraceptive method within 2 years postpartum (vaginal, 27.7%; caesarean, 40.1%; p=0.0025). Compared with women who had VD, those who had CS had significantly higher odds of postpartum contraceptive use (adjusted OR (aOR) = 1.52; 95% CI 1.03 to 2.25). However, when disaggregated by contraceptive method choice, the associations were not statistically significant: least effective methods (aOR=1.37; 95% CI 0.71 to 2.66), moderately effective methods (aOR=1.49; 95% CI 0.89 to 2.52) and most effective methods (aOR=1.84; 95% CI 0.97 to 3.49), although all estimates were suggestive of higher odds among caesarean births.Conclusion Caesarean delivery was independently associated with higher overall postpartum contraceptive use and showed a positive—though not statistically significant—association with the use of least, moderately and most effective methods. These findings underscore the importance of person-centred counselling to ensure that all postpartum women, regardless of delivery mode, receive comprehensive information on the full range of contraceptive options, thereby promoting informed choice and equitable access.